2017
DOI: 10.22547/ber/9.3.2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Social Responsibility on Default Risk: Empirical evidence from US Firms

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Dewaelheyns and Hulle [25] argued the likelihood of a default decreases when the return on assets improves. Companies that are profitable often have a lower likelihood of defaulting on their debt commitments because profitable companies create larger cash flows, which may be utilized to pay down their debt obligations [27]. Hamid and Siddiqui [28] using data of Pakistani Non-financial firms found that firms with high level of profitability, Cash Flows, liquidity and growth rate are less risky as compared to firms with lower levels of profitability, liquidity and growth rate.…”
Section: Firm Specific Determinants Of Probability Of Defaultmentioning
confidence: 99%
See 1 more Smart Citation
“…Dewaelheyns and Hulle [25] argued the likelihood of a default decreases when the return on assets improves. Companies that are profitable often have a lower likelihood of defaulting on their debt commitments because profitable companies create larger cash flows, which may be utilized to pay down their debt obligations [27]. Hamid and Siddiqui [28] using data of Pakistani Non-financial firms found that firms with high level of profitability, Cash Flows, liquidity and growth rate are less risky as compared to firms with lower levels of profitability, liquidity and growth rate.…”
Section: Firm Specific Determinants Of Probability Of Defaultmentioning
confidence: 99%
“…One of the variables that affects a firm's likelihood of default is its size [27]. According to the trade-off argument, large companies typically have higher debt ratios because they have less information asymmetry.…”
Section: Firm Specific Determinants Of Probability Of Defaultmentioning
confidence: 99%